Questions and answers : - Ligouri, Gary (McGaw Hill, 2014)
Questions and Answers: A Guide to Fitness and Wellness delivers the serious content you want in a Student Question and Answer format that’s fun to read and an online learning space that commands active learning. We began by collecting over 1,000 Fitness and Wellness questions asked by real students. Questions like, “How can I improve my self-esteem?” or “Do I really need 8 glasses of water a day?” introduce each section of material throughout the program.